1957
DOI: 10.1149/1.2428601
|View full text |Cite
|
Sign up to set email alerts
|

Closure to “Discussion of ‘A Mechanism for the Anodic Dissolution of Magnesium’ [J. H. Greenblatt (pp. 539–543, Vol. 103)]”

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1958
1958
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The current efficiency of Mg in 3 % NaC1 solution assuming a Mg valency of two is approximately 50% and is independent of temperature in the range 0~176 (8). The current efficiency of Mg in 3 % NaC1 solution assuming a Mg valency of two is approximately 50% and is independent of temperature in the range 0~176 (8).…”
Section: May 1958mentioning
confidence: 96%
See 3 more Smart Citations
“…The current efficiency of Mg in 3 % NaC1 solution assuming a Mg valency of two is approximately 50% and is independent of temperature in the range 0~176 (8). The current efficiency of Mg in 3 % NaC1 solution assuming a Mg valency of two is approximately 50% and is independent of temperature in the range 0~176 (8).…”
Section: May 1958mentioning
confidence: 96%
“…This paper was prepared for delivery before the Buffalo Meeting, Oct. [6][7][8][9][10] 1957. This paper was prepared for delivery before the Buffalo Meeting, Oct. [6][7][8][9][10] 1957.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reports using a murine vation of TNF. Antibody response to PGPS has been investigated in some diseases [31][32][33], but the re-model showed excision and grafting with syngeneic skin was itself suppressive in cell-mediated immunity sponse after burn injury has never been examined but by our laboratory. Our previous studies have shown and that the suppression was additive to that of burn injury [22,23].…”
Section: Resultsmentioning
confidence: 99%